Keputusan Konsumen Memilih Ayam Goreng Tepung Siap Saji: Studi Kasus Pada Waralaba Produk Lokal Bali Jaya Fried Chicken - Ida Ayu Trisna Wijayanthi; Ni Putu Rianasari (Jurnal REKOMEN (Riset Ekonomi Manajemen), 2020)
This study aims to determine the consumer's decision to choose Ready-Fried Flour Chicken and the dominant factor influencing consumers to choose Ready-Fried Flour Chicken in the Bali Local product franchise, a case study on Jaya Fried Chicken (JFC). The research method used was a questionnaire with 130 respondents taken using accidental sampling techniques. The variables used were 26 variables which were described based on Marketing Mix and Consumer Behavior. The research data were processed using Factor analysis, resulting in 6 (six) formed factors, namely the Speed of Service Factor with an eigen value of 8,560, a Reference Group Factor with an eigen value of 2,857, a Location Factor with an eigen value of 1,970, a Product Taste Factor with an eigen value equal to 1,388, Advertising Factor with eigen value of 1,214, and Consumer Revenue Factor with eigen value of 1,017. Based on the Percent of Variance it can be stated that the Speed of Service factor is the most representative (dominant) factor of the factors that influence consumers' decision to choose ready-to-eat fried chicken: a case study on a local product franchise Bali Jaya Fried Chicken because it is able to contribute a part of the variation that is the largest of all observed variations is 32.922% of the total 72.410% of variants.